Statement of Peer Review - Diane Ashiru-Oredope; Carry Triggs-Hodge; Jordan Charlesworth (Medical Sciences Forum, 2023)
In submitting conference proceedings to Medical Sciences Forum, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]